INISIASI PEMASARAN DIGITAL UMKM KERIPIK TEMPE “ASYIQ” DAN POPCORN “MAS POP” DESA JONO TAWANGHARJO GROBOGAN - Syamsul Hadi; Atina Alfadela; Livy Febria Tedjamulia; Khafidz Abdulah Budianto; Dian Chairun Nisa; Hisanin Tsaqifa Diasty; Titin Putri Dhaniati; Islamiani Syanindita Farahdiba; Aldo Tri Pangestu; Herlambang Adi Wicaksono (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Digital Marketing activities have the aim of helping SMEs "Asyiq" Tempe Chips and "Mas Pop" Popcorn business actors use social media and e-commerce to promote their products so that the wider community can know them. Digital marketing activities are conducted using lectures, discussions, and training methods for the relevant UMKM partners. The participation and enthusiasm of the "Asyiq" Tempe Chips and "Mas Pop" UMKM business owners in digital marketing activities are excellent. Partners, in this case, are very open and enthusiastic about receiving input and knowledge about marketing methods through digital marketing. Partners in this activity then actively practice the knowledge that has been given about digital marketing. The impact of this digital marketing activity can increase understanding and the economy for UMKM partners because digital marketing will certainly expand their market share so that the wider community can know it. Digital marketing activities at UMKM "Asyiq" Tempe Chips and "Mas Pop" Popcorn are expected to benefit and be sustainable.